2016
DOI: 10.1021/acs.biochem.6b00976
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl 4-Hydroxylase: Substrate Isosteres in Which an (E)- or (Z)-Alkene Replaces the Prolyl Peptide Bond

Abstract: Collagen prolyl 4-hydroxylases (CP4Hs) catalyze a prevalent posttranslational modification—the hydroxylation of (2S)-proline residues in protocollagen strands. The ensuing (2S,4R)-4-hydroxyproline residues are necessary for the conformational stability of the collagen triple helix. Prolyl peptide bonds isomerize between cis and trans isomers, and the preference of the enzyme is unknown. We synthesized alkene isosteres of the cis and trans isomers to probe the conformational preferences of human CP4H1. We disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…26,30,31 The peptide bond of the Pro residue that is bound in the enzymic active site is likely in the cis (that is, E ) conformation. 32,33 After formation of the ferryl ion and subsequent hydroxylation of the Pro residue, the enzyme releases the nascent Hyp-containing strand and succinate.…”
Section: Cp4h Mechanismmentioning
confidence: 99%
“…26,30,31 The peptide bond of the Pro residue that is bound in the enzymic active site is likely in the cis (that is, E ) conformation. 32,33 After formation of the ferryl ion and subsequent hydroxylation of the Pro residue, the enzyme releases the nascent Hyp-containing strand and succinate.…”
Section: Cp4h Mechanismmentioning
confidence: 99%
“…Nonheme iron dioxygenases play an important role in all forms of life, where they take part in biochemical transformations, such as the biosynthesis of natural products and antibiotics as well as DNA repair mechanisms. For instance, in mammals, 4-hydroxyproline is formed from proline on a nonheme iron dioxygenase, while in plants the flavonol biosynthesis pathway includes a cascade of reactions by several nonheme iron dioxygenases that perform a selective substrate hydroxylation or desaturation reaction. Among the class of nonheme iron dioxygenases are the group of ferrous iron/α-ketoglutarate-dependent dioxygenases that utilize α-ketoglutarate (αKG, also called 2-oxoglutarate) and dioxygen. , They activate a range of substrates and catalyze a variety of chemical reactions comprising substrate hydroxylation, cyclization, halogenation, rearrangement, and desaturation, mostly centered on inactivated carbon centers of aliphatic groups. …”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical studies have been reported on the catalytic reaction mechanism of nonheme iron dioxygenases, and a consensus mechanism involves the binding of dioxygen to the iron center followed by decarboxylation of αKG to form succinate and the formation of an iron­(IV)-oxo species, which is believed to be the active oxidant. In this work, we investigated the hydrogen-atom abstraction pathways of l -Arg and l -homo-Arg from the C 3 - and C 4 -positions and the subsequent mechanisms leading to C 3 - and C 4 -hydroxylation and C 3 –C 4 -desaturation.…”
Section: Introductionmentioning
confidence: 99%
“…Following this study, they successfully extended the strategy to the synthesis of related analogs. , Finally, Raines synthesized cis- and trans- diproline isosteres and showed which conformation of the native peptidyl bond is preferentially recognized by collagen prolyl 4-hydroxylase. It also strengthened the idea that alkenes could be made use of as replacements for peptide bonds (Figure H) …”
Section: Introductionmentioning
confidence: 99%